The Efficacy of Ultrasound, Pulsed Shortwave Diathermy and Bicycle Exercises in Knee Osteoarthritis (Annals of Medical Research, 2021)
None
Keywords: Knee Osteoarthritis, Bicycle Exercises, Ultrasound, Pulsed Shortwave Diathermy